Pendidikan Islam Perspektif Syekh An-Nawawi Al-Bantani - Mapatih (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2019)
Sheikh Nawawi al-Bantani is a legendary scholar and intellectual. Through his works worldwide in various fields, making it a role model by many hunters of science. In addition to the religious sciences, he is also an expert in the field of education. His educational thoughts are very cumulative, starting from basic ideas, values, to guidelines for learning activities in Islam. The basis is the study of classical, middle and modern thinkers who are then integrated with their own ideas. Making the results of his thinking very reality and can meet the needs of practitioners of Islamic education. Coupled with a foundation of religious knowledge and a deep understanding of Islamic laws, as well as the influence of the teachers so as to form a mature character. Sheikh Nawawi with his educational thoughts has provided many conceptualizations of Islamic education to date. Education thinking is still relevant to be applied both concerning basic values ​​and Islamic educational activities in Indonesian religious and plural society. Among these principles are three integral dimensions namely theocentric dimension, anthropocentric dimension, and the sunnatullah dimension, which can be applied in the current educational process. good if it is continued by outlining his ideas to be more operational. Even though these ideas originated from Islamic education thinkers in the 19th century, substantive matters are still relevant, especially in Islamic education in Indonesia.